FACTORS CONTRIBUTING TO THE ESCALATION OF ALCOHOL CONSUMPTION. (January 2022) - Bowen, Michael T.; George, Olivier; Muskiewicz, Dawn E.; Hall, F. Scott
Highlights: Much work examines acquisition and initial escalation of alcohol consumption. Considerably less work has focused on escalation most relevant to alcohol use disorder. Many complex, interacting factors influence escalation of alcohol consumption. Studying these factors is key to understanding how individuals develop alcohol use disorder. They might also pave the way for better, more personalised treatments. Abstract: Understanding factors that contribute to the escalation of alcohol consumption is key to understanding how an individual transitions from non/social drinking to AUD and to providing better treatment. In this review, we discuss how the way ethanol is consumed as well as individual and environmental factors contribute to the escalation of ethanol consumption from intermittent low levels to consistently high levels. Moreover, we discuss how these factors are modelled in animals. It is clear a vast array of complex, interacting factors influence changes in alcohol consumption. Some of these factors act early in the acquisition of ethanol consumption and initial escalation, while others contribute to escalation of ethanol consumption at a later stage and are involved in the development of alcohol dependence. There is considerable need for more studies examining escalation associated with the formation of dependence and other hallmark features of AUD, especially studies examining mechanisms, as it is of considerable relevance to understanding and treating AUD.